Conservation status of newly discovered subpopulations of two globally threatened tree species in the East Usambara Mountains, Tanzania - Henry J. Ndangalasi; Norbert J. Cordeiro (Oryx)
Two globally threatened tree species, the Critically Endangered Cola porphyrantha (Malvaceae) and the Endangered Gigasiphon macrosiphon (Fabaceae) are narrowly distributed in Kenya and Tanzania. In Tanzania, both species were first located in an isolated, unprotected forest fragment in the East Usambara Mountains in the early 2000s. As no assessment of these subpopulations had been made since then, we surveyed the forest fragment as well as nearby unprotected forest fragments. In contrast to the early 2000s when only five and two mature trees of C. porphyrantha and G. macrosiphon, respectively, were located, we found 18 and five mature trees of these species. We did not find either species in intensive surveys of seven neighbouring unprotected forest fragments but we located a single G. macrosiphon beside a river close to one of the unprotected fragments. Gigasiphon macrosiphon was also previously known from two sites in Amani Nature Reserve in the East Usambara Mountains, but recent surveys, including our own, failed to relocate these subpopulations. Because of heavy anthropogenic disturbance in the one site where the two species still occur and their general absence from adjacent forest, we are working with the local community to protect the isolated fragment. Additionally, in situ planting of locally grown seedlings of both species is being supported by Amani Nature Reserve.